University proceedings. Volga region. Technical sciences - Yu.P. Perelygin (Известия высших учебных заведений. Поволжский регион:Технические науки)
Background. Bimetallic copper-aluminum adapters are used in industrial installations, power supply systems of buildings, vehicles, household appliances and other devices. The main technologies for producing copper-aluminum composite materials today are surfacing, pressure welding, cast cladding, batch welding by rolling. However, the above technologies do not allow to ensure the high quality of the composite, and in some cases absolutely cannot be used to obtain it. In this regard, the most promising technology for producing a copper-aluminum composite is explosion welding. The purpose of the work is to assess the complex of physical and mechanical properties obtained by explosion welding of a copper-aluminum composite material. Materials and methods. The main approach to achieve this goal is to conduct a set of studies of physical and mechanical properties with the determination of the strength of the weld, microhardness, microstructure of the composite material, quantitative assessment of the chemical composition of the composite and the seam zone, the magnitude of electrical resistance. The study of the above properties was carried out according to the methods in accordance with GOST on the verified equipment by certified personnel. Results. Evaluation of the complex of physical and mechanical properties made it possible to choose a rational mode of explosion welding, which ensures the best strength indicators of the composite. Evaluation of microhardness, microstructure and quantitative evaluation of the chemical composition of the composite and its near-weld zone made it possible to determine the nature of material hardening and the properties of intermetallic phases in the weld zone. Investigation of the electrical resistance value of the composite material showed that the transient electrical resistance of the bimetal copperaluminum primary winding of the transformer is higher than the transient electrical resistance of the bimetal copper-aluminum obtained by explosion welding. Conclusions. The use of a bimetal obtained by explosion welding in the manufacture of transitional bimetal copper-aluminum washers for electrical purposes made it possible to increase the strength of the connection to values higher than the strength of aluminum, reduce the transitional electrical resistance from 2 to 5 times in comparison with a similar bimetal obtained using traditional technology, increase the service life of products.